2006
DOI: 10.1161/circulationaha.105.575118
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Bone Marrow Cell Transfer After Myocardial Infarction

Abstract: Background-Intracoronary transfer of autologous bone marrow cells (BMCs) may enhance recovery of left ventricular (LV) function in patients after acute myocardial infarction (AMI). However, clinical studies addressing the effects of BMCs after AMI have covered only limited time frames ranging from 3 to 6 months. The critical question of whether BMC transfer can have a sustained impact on LV function remains unanswered. Methods and Results-After percutaneous coronary intervention with stent implantation (PCI) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 884 publications
(156 citation statements)
references
References 32 publications
7
146
1
2
Order By: Relevance
“…We have previously shown that intracoronary infusion of autologous BMCs enhances the recovery of systolic function in postinfarct patients, 13,44 and we have identified FGF9 as a factor that is secreted from these cells. 14 Given the results of the present study, FGF9-mediated paracrine effects in the border zone of the infarct may contribute to the improvements in microvascular perfusion and regional contractility that have been observed after intracoronary BMC transfer in some clinical trials.…”
Section: Korf-klingebiel Et Al Fgf9 Improves Outcome After MI 511mentioning
confidence: 84%
“…We have previously shown that intracoronary infusion of autologous BMCs enhances the recovery of systolic function in postinfarct patients, 13,44 and we have identified FGF9 as a factor that is secreted from these cells. 14 Given the results of the present study, FGF9-mediated paracrine effects in the border zone of the infarct may contribute to the improvements in microvascular perfusion and regional contractility that have been observed after intracoronary BMC transfer in some clinical trials.…”
Section: Korf-klingebiel Et Al Fgf9 Improves Outcome After MI 511mentioning
confidence: 84%
“…21) However, recent studies have provided conflicting results. [22][23][24] In addition, there have been few reports concerning the therapeutic potential of MSC transplantation for nonischemic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived mesenchymal stem cells (MSCs) are considered effective in myocardial infarction therapies both in basic research studies (Amado et al, 2005;Tang et al, 2006) and in clinical trials (Janssens et al, 2006;Meyer et al, 2006). MSCs repair the ischemic myocardium primarily by angioblast-mediated vasculogenesis (Kocher et al, 2001), prevention of apoptosis of native cardiomyocytes, or by direct regeneration of the lost cardiomyocytes (Shim et al, 2004;Takahashi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%